Bullying Behavior in Generation Z Youth: Case Study at Palu City DP3A Children's Forum - Arwan, Arwan; Arif, Syamsul; Syam, Sadli; Napirah, Muhammad Ryman; Krisnasari, Sendhy; Firmansyah , Firmansyah; Suwendro, Novi Inriyanny (Journal of Health and Nutrition Research, 2023)
This research aims to determine bullying behavior among Generation Z youth at the DP3A Children's Forum in Palu City. This research used qualitative research methods with a case study design. There were 10 informants in the research using purposive sampling techniques. Data management using matrix techniques. The results of research on the behavioral belief variable were that the perpetrator understands the dangers of bullying quite well, but bullying behavior was still carried out. Regarding the evaluation variable or behavioral impact, most did not know and did not feel the impact of bullying. In the behavioral motivation variable, the perpetrators were motivated to bully because it was fun for them and had thought about stopping bullying because they had received warnings and advice from those closest to them. It is suggested that the Women's Empowerment and Child Protection Service (in Indonesia known as DP3A) of Palu City should find out about providing maximum education and guidance to the parents of the perpetrators so that bullying behavior by those who become administrators or new members in the Palu City Nosarara children's forum does not occur. Parents should pay attention and always ask about the activities they are carrying out and understand their children's feelings so that they trust them and do not hesitate to talk about their children's problems